Los procesos cognitivos básicos y la comprensión lectora en estudiantes de primer ciclo de la carrera de educación especial, de la Facultad de la Educación, el Arte y la Comunicación, 2023-2024 - Pacheco Japón, Gissela Noemí (2024)
The general objective of the curricular integration work entitled: Basic cognitive processes and reading comprehension in first cycle students of the special education course at the Faculty of Education, Art and Communication, 2023-2024, was to analyse the relationship between the level of the basic cognitive processes of attention and memory and reading comprehension in its levels: literal, reorganisation of information, inferential, critical and appreciation in first cycle students of the special education course at the Faculty of Education, Art and Communication, 2023-2024. The research responds to a quantitative approach of a descriptive, correlational and transversal type, with a non-experimental design. The d2 test, which assesses attention, the memory subscale of the RIAS test, and the ICLAU to assess reading comprehension were applied to a sample of 36 students. Kendall's rank correlation coefficient was used to measure the degree of association between the variables. The findings showed that 97% of those investigated had a low level of attention; 56% had a low level of memory; and 84% of those investigated had a medium level of reading comprehension. Finally, it is concluded that there is no correlation between the cognitive process of attention and reading comprehension, according to the statistical value of Kendall's correlation coefficient of 0.000; while, on the other hand, through a statistical value of Kendall's correlation coefficient of 0.268 it was shown that there is a low positive correlation between the cognitive process of memory and reading comprehension.